ADAPTATION AND IMPROVEMENT OF STAFF STIMULATION AND MOTIVATION SYSTEM TO ENVIRONMENTAL CHANGES - D. A. Lukashevskaya (Вестник университета)
The scope of the concepts of “adaptation”, “improvement”, “stimulation” and “motivation” of staff to various changes in the professional environment has been analysed. The objective need to adapt the incentive system and staff motivation to new conditions for the functioning of the enterprise has been considered. The differentiating features of each phenomenon are traced in scientific discourse and in practice have been traced. A set of measures to improve the system of stimulation of working personnel and adaptation in the synthesis with motivational mechanisms has been proposed. The main conclusions and suggestions can be used in the activities of related organizations in order to improve the system of incentives for workers.